2020
DOI: 10.1155/2020/8881270
|View full text |Cite
|
Sign up to set email alerts
|

Antiphotoaging Potential of Extracts of Yin‐Tonic Herbal Medicine in Skin Cell and Human Skin Equivalent

Abstract: Yin-tonic herbal medicines have been shown to possess properties that make skin healthy by nourishing within various organs of the body. However, the antiphotoaging effect of these medicines on the skin has not been fully studied. Photoaging occurs with prolonged sun exposure and causes skin damage and aging, with depletion of the dermal extracellular matrix and chronic alterations in skin structure, such as wrinkles. In this study, we assessed the antiphotoaging effects of eight yin-tonic herbal medicines on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…To prevent skin damage caused by UV-induced excessive levels of ROS and to regulate epidermal homeostasis, skin cells activate their endogenous defense system and exert their antioxidant function [ 37 ]. The results of our experiments showed that RES preadministration balanced intracellular oxidative stress by increasing GSSH levels and enhancing SOD activity, as well as by reducing ROS levels, while promoting the expression of mRNA for GPX-4 and HO-1 and the nuclear Nrf2 protein, and by promoting the expression of mRNA for Nrf2 and its downstream genes HO-1, NQO1, SOD1, and GPX-4, balancing oxidative stress in the skin of photoaged mice.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent skin damage caused by UV-induced excessive levels of ROS and to regulate epidermal homeostasis, skin cells activate their endogenous defense system and exert their antioxidant function [ 37 ]. The results of our experiments showed that RES preadministration balanced intracellular oxidative stress by increasing GSSH levels and enhancing SOD activity, as well as by reducing ROS levels, while promoting the expression of mRNA for GPX-4 and HO-1 and the nuclear Nrf2 protein, and by promoting the expression of mRNA for Nrf2 and its downstream genes HO-1, NQO1, SOD1, and GPX-4, balancing oxidative stress in the skin of photoaged mice.…”
Section: Discussionmentioning
confidence: 99%
“… 48 SGM is composed of Red Ginseng, Ophiopogonis Radix, and Schisandrae Chinensis Fructus. Here, Ophiopogonis Radix nourishes the yin (nutrition and fluid in the human body, which nourishes various organs 49 ), Schisandrae Chinensis Fructus astringents the qi (vital energy, regarded as a driving force of biological activities in the human body, including both nutrient substances and organ functions 50 ) and has antitussive effects, and Red Ginseng tonifies qi and enhances immunity. 51 The combination of these herbs affects the respiratory center and then relieves dyspnea in COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The skin tissues were cultured in maintenance medium provided by the manufacturer and incubated at 37 °C with 5% CO 2 . The cytotoxicity of SNPs was measured by using MTT assays according to the manufacturer’s protocol [ 49 ]. Skin tissues were treated with SNPs or commercially available emulsifiers for 24 h. After incubation with MTT solution (25 mg/mL in PBS) diluted to 0.3 mg/mL in maintenance medium at 37 °C for 4 h, purple formazan was formed in the tissues.…”
Section: Methodsmentioning
confidence: 99%